Adsorption and Desorption Properties of Beta-Carotene in Crude Palm Oil (CPO) Using Empty Fruit Bunch-Based Activated Carbon Composite with Metal-Organic Frameworks (MOFs) - Fe(TAC) - Yunita Dwi Utami; Trivena Myta Br. Manik; Frengky Sanjaya Ginting; Chyntya Angelina PN; Sri Rahayu; Syafrina Letare Lubis; Jasmidi; Rini Selly; Putri Faradilla; Moondra Zubir (Universitas Negeri Medan, 2025)
The rapid expansion of oil palm plantations in North Sumatra, from 31,730,961 hectares in 2016 to 41,667,011 hectares in 2018, has resulted in significant solid waste generation, particularly empty fruit bunches (EFB). This study aims to utilize EFB as a precursor for activated carbon production and evaluate its effectiveness in adsorbing beta-carotene from crude palm oil (CPO). EFB was processed through carbonization and activation to create a composite adsorbent KA-Fe(TAC) synthesized with metal-organic frameworks (MOFs). Characterization using X-ray diffraction (XRD) confirmed the crystalline structure of the composite. Results indicated that the optimal adsorption efficiency for activated carbon was 8.925%, while the KA-Fe(TAC) composite achieved 21.645%. The findings suggest that the KA-Fe(TAC) composite significantly enhances beta-carotene adsorption capacity compared to conventional activated carbon. Additionally, the optimal contact time for adsorption was found to be 60 minutes for activated carbon and 150 minutes for the KA-Fe(TAC) composite, indicating improved efficiency over time.